Recommendations for blood pressure measurement in large arms in research and clinical practice: position paper of the European society of hypertension working group on blood pressure monitoring and cardiovascular variability. Issue 7 (July 2020) - Palatini, Paolo; Asmar, Roland; O'Brien, Eoin; Padwal, Raj; Parati, Gianfranco; Sarkis, Josh; Stergiou, George
Abstract : N/A: Blood pressure measurement in obese individuals can be challenging because of the difficulty in properly cuffing large upper arms. Achieving a proper cuff fit can be problematic especially in people with a shorter arm length relative to circumference. This expert statement provides recommendations on blood pressure measurement in large arms for clinical use and research purposes. Tronco-conically shaped cuffs should be used in people with large arms, especially with arm circumferences greater than 42 cm as they better fit on the conical arm shape. Cuffs with frustum of the cone slant angle of 85° should satisfy most conditions. In individuals with short upper-arm that does not allow application of a properly sized cuff, wrist or forearm measurement might be used in clinical practice, but not for validation of automatic devices. Wide-range cuffs coupled to oscillometric devices provided with special software algorithms can also be used as alternatives to standard cuff measurement, provided they are independently validated per AAMI/ISO 81060-2 protocol. For validation studies, the intraarterial measurement is generally considered as the gold standard, yet for possible methodological pitfalls and ethical concerns, it is not recommended as the method of choice. Tronco-conical cuffs with inflatable bladder dimensions of 37–50 × 75–100% arm circumference should be used for reference auscultatory blood pressure measurement wherever the upper arm length allows a proper fit. There is a need for future studies that help identify the optimal shape of cuffs and bladders investigating the influence of sex, age, arm physical properties, and artery characteristics.